The mythical figure of the first man. Looking at "Adam" by Leopold Staff through the prism of myth analysis - Badowska, Katarzyna (Prace Polonistyczne, 2023)
Using mythanalysis, Badowska interprets one of Leopold Staff’s mature poems Adam (1914), which presents a poetic monologue delivered by a corpse that rests in a grave. The corpse’s ontological situation is a consequence of breaking the prohibition mentioned in the myth of the fall in the Book of Genesis. Badowska notes that the images and symbols used by the poet belong, according to Durand’s classification, to the diurnal order. She also argues that in Adam, as in many other poems by Staff, the author’s imagination is organized according to the vertical model of space, which is based on the archetypal binary juxtaposition of the negatively valued bottom and the positively valued top. She concludes that Staff’s poem does not retell the Adamic myth, but serves as a version of the heroic myth, which features the rites of regression, symbolic death (katodos), and the subsequent rebirth (anodos).